Descriptive Analysis of the Characteristics of Patients’ Referral from Matsu Islands to Taiwan: A Single Medical Center Experience - Yi-Pang Lo; Chung-Yu Lai; Ping-Hsuan Hsieh; Yen-Chiao Huang; Yin-Chung Chen; Shih-Hung Tsai (Journal of Medical Sciences)
Background: Patients at the offshore islands need to be transported to the Taiwan mainland to be able to reach the advanced health-care facilities. Aim: The purpose of this study was to identify the characteristics of patients transferred from Matsu islands to a medical center. Methods: This study was conducted at a medical center in the northern Taipei City. Medical records were reviewed from the department of emergency medicine and hospitalization system. Adult patients over 18 years old were enrolled between January 2019 and September 2023. All the data were handled using the SPSS version 24.0 software (IBM, Armonk, NY, USA). Results: Of the 316 adult patents, with the majority being more than 50 years old, male, and local residents. There were a total of 500 visits including the hospitalization from the emergency department (ED) (61.4%), hospitalization from the outpatient department (30.6%), and only visit to the ED (8.0%). Dominant reasons were injury, poisoning, and certain other consequences of external causes (23.6%), neoplasms (16.0%), and diseases of the circulatory system (11.8%). Nearly half of the visits (46.6%) needed the operation therapy, 15% of patents were disposed to the intensive care unit, and a large proportion of them (36.8%) accepted the treatment from the different specialties. Conclusion: Our results have illustrated the features of medical utilization of the patients from Matsu islands. Injury was the main cause which led to the advanced medical care. In addition, the necessity of the multidisciplinary care was also observed from the medical records.